Равномерная и касательная аппроксимация на полосе мероморфными функциями, имеющими оптимальный рост - С. Алексанян (Հայաստանի ԳԱԱ)
Пусть функция f непрерывна на закрытой полосе Sh = { z :│Imz│ ≤ h } и голоморфна в ее внутренности. В работе исследуется задача равномерного и касательного приближения функции f мероморными функциями g с наилучшей оценкой роста g с наилучшей оценкой роста g в терминах неванлинновской характеристики T(r, g). Этот рост зависит от роста f на Sh и дифференциальных свойств f на dSh. Предполагается, что возможные полюсы g лежат только на мнимой оси. The paper discusses the problem of approximation of functions continuous on a closed stripe Sh = { z :│Imz│ ≤ h } and holomorphic in its interior. The results relate to the uniform and tangential approximation of such functions f by meromorphic functions g with minimal growth in terms of Nevanlinna characteristic T(r; g). The growth depends on the growth of f in Sh and certain differential properties of f on δSh. It is assumed that the possible poles of g are restricted to the imaginary axis.
Keywords: Mathematics; Science